DK knowledge genius! - Chrisp, Peter; Gifford, Clive; Harvey, Derek; Mills, Andrea; Woodward, John, 1954- (DK Publishing, 2019)
Presents a visual encyclopedia of quizzes and picture puzzles to test readers' trivia knowledge on a range of topics, from geography--like finding the Amazon River on a world map--to sports--like being able to tell the difference between a tennis ball and a baseball.